APOLOGY STRATEGY, SOURCE CREDIBILITY, AND ORGANIZATIONAL REPUTATION: A CRISIS COMMUNICATION EXPERIMENT ON THE MAKAN BERGIZI GRATIS (MBG) PROGRAM IN WEST JAVA - Dary Farah Fikriyyah; Dian Wardiana Sjuchro; Heru Ryanto Budiana (SOSIOEDUKASI, 2026)
This study examines the effects of apology message type and source credibility on organizational reputation during a public sector crisis. Using Situational Crisis Communication Theory (SCCT) and source credibility theory, a 2 × 2 between-subjects experiment was conducted with 160 Generation Z participants in West Java. Participants were exposed to simulated crisis scenarios involving a mass food poisoning incident in Indonesia’s Free Nutritious Meal (Makan Bergizi Gratis/MBG) program. Data were analyzed using Two-Way ANOVA. The findings show that apology message type did not significantly affect organizational reputation (F(1,156) = 1.284, p = 0.259). However, source credibility had a significant effect (F(1,156) = 8.580, p = 0.004, ηp² = 0.052), with official government sources producing more favorable reputation evaluations than influencers. No significant interaction effect was found between apology message type and source credibility (F(1,156) = 0.120, p = 0.730). Additional analyses suggest that participants’ prior attitudes toward the MBG program may also influence reputation assessments. The results indicate that, in public sector crises involving public safety concerns, source credibility is more influential than message variation in shaping organizational reputation. The study contributes to crisis communication research and offers practical implications for government institutions seeking to maintain public trust during crises. Keywords: Apology Strategy, Source Credibility, Organizational Reputation, Public Sector Crisis, Generation Z.